Investigation of crystalline lens overshooting: ex vivo experiment and optomechanical simulation results - Dahaghin, Ali; Salimibani, Milad; Boszczyk, Agnieszka; Jóźwik, Agnieszka; Skrok, Marta; Grasa, Jorge; Siedlecki, Damian (Frontiers in Bioengineering and Biotechnology, 2024)
Crystalline lens overshooting refers to a situation in which the lens momentarily shifts too much from its typical location immediately after stopping the rotational movement of the eye globe. This movement can be observed using an optical-based technique called Purkinje imaging. In this work, an experimental setup was designed to reproduce ex vivo this effect using a fresh porcine eye. The sample was rotated 90 degrees around its centroid by means of a high-velocity rotational stage, and the Purkinje image sequences were recorded allowing to quantify the overshooting effect. The numerical part of the study consisted of developing a computational model of the eye, based on the finite element method, that allowed to understand the biomechanical behaviour of the different tissues in this dynamic scenario. A 2D fluid-structure interaction model of the porcine eye globe, considering both the solid parts and humours, was created to reproduce the experimental outcomes.Outputs of the simulation were analysed using an optical simulation software to assess whether the mechanical model behaves optically like the real ex vivo eye. The simulation predicted the experimental results by carefully adjusting the mechanical properties of the zonule fibres and the damping factor. This study effectively demonstrates the importance of characterizing the dynamic mechanical properties of the eye tissues to properly comprehend and predict the overshooting effect.